2003
DOI: 10.1161/01.atv.0000073314.51987.84
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Activation of Ras by Fluid Flow Is Mediated by Gα q and Gβγ Subunits of Heterotrimeric G Proteins in Human Endothelial Cells

Abstract: These results suggest that the rapid, shear-induced activation of Ras is mediated by Galpha(q) through the activity of Gbetagamma subunits in human vascular endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…This activation may be even more extensive as recently shear was shown to have downstream effects that required Gα(q) and Gβγ to activate Ras itself (Gudi et al, 2003). While this specific activation has not been shown in bone cells, as we have stated, mechanically responsive systems appear to be somewhat universal with regard to cells and are likely to be true for osteoblasts and osteocytes.…”
Section: Signaling Through G-proteinsmentioning
confidence: 66%
See 1 more Smart Citation
“…This activation may be even more extensive as recently shear was shown to have downstream effects that required Gα(q) and Gβγ to activate Ras itself (Gudi et al, 2003). While this specific activation has not been shown in bone cells, as we have stated, mechanically responsive systems appear to be somewhat universal with regard to cells and are likely to be true for osteoblasts and osteocytes.…”
Section: Signaling Through G-proteinsmentioning
confidence: 66%
“…In essence, mechanical forces have been shown to activate every type of signal transduction cascade, from increases in intracellular cAMP (Lavandero et al, 1993), IP3 and intracellular calcium (Dassouli et al, 1993;Li et al, 2004), guanine regulatory proteins (Gudi et al, 2003), and MAPK (Rubin et al, 2002c). As previously stated, this review does not aim to collect each and every report of each signal cascade stimulated by mechanical force in bone cells.…”
Section: Mechanically Activated Intracellular Signaling Systemsmentioning
confidence: 99%
“…The shear-stress-induced tyrosine phosphorylation of PECAM-1 is a delayed phenomenon relative to the activation of Ras (Gudi et al, 2003) or of K + channels (Olesen et al, 1988) and the fact that a tyrosine kinase must be activated in order for PECAM-1 to be phosphorylated means it is unlikely that PECAM-1 acts as a mechanoreceptor per se. Indeed, fluid shear stress elicits the tyrosine phosphorylation of PECAM-1 mutants that lack the transmembrane domain of the adhesion molecule and that do not localize to the lateral membranes or participate in cell-cell homophilic PECAM-1 binding (Kaufman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of endothelial cells with anti-sense G q oligonucleotides inhibits shear stress-induced Ras-GTPase activity, while the transfection of G 1 2 enhances the shear stress-induced Ras activation [78]. It has also been reported that the shear stress-mediated activation of ERK1/2 is abolished by the treatment of endothelial cells with the G i inhibitor pertussis toxin [79].…”
Section: G-protein-coupled Receptors (Gpcrs) and G Proteinsmentioning
confidence: 99%